Neonatal encephalopathy multiorgan scoring systems: systematic review - Razif, Noor Adeebah Mohamed; D’Arcy, Aidan; Waicus, Sarah; Agostinis, Alyssa; Scheepers, Rachelle; Buttle, Yvonne; Pepper, Aidan; Hughes, Aisling; Fouda, Basem; Matreja, Panya; MacInnis, Emily; O’Dea, Mary; et al. (Frontiers in Pediatrics, 2024)
Neonatal encephalopathy (NE) is a condition with multifactorial etiology that causes multiorgan injury to neonates. The severity of multiorgan dysfunction (MOD) in NE varies with therapeutic hypothermia (TH) as the standard of care. The aim is to identify current approaches used to assess and determine an optimum scoring system for MOD in NE.The systematic review conformed to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. An electronic search was conducted using PubMed, EMBASE, MEDLINE, Cochrane Central Register of Controlled Trials, Scopus, and CINAHL for studies of scoring systems for MOD in NE.The search yielded 628 articles of which 12 studies were included for data extraction and analysis. Five studies found a positive correlation between the severity of NE and MOD. There was significant heterogeneity across the scoring systems, including the eligibility criteria for participants, the methods assessing specific organ systems, the length of follow-up, and adverse outcomes. The neurological, hepatic, cardiovascular, respiratory, hematological, and renal systems were included in most studies while the gastrointestinal system was only in three studies. The definitions for hepatic, renal, and respiratory systems dysfunction were most consistent while the cardiovascular system varied the most.A NE multiorgan scoring system should ideally include the renal, hepatic, respiratory, neurological, hematological, and cardiovascular systems. Despite the heterogeneity between the studies, these provide potential candidates for the standardization of MOD scoring systems in NE. Validation is needed for the parameters with adequate length of follow-up beyond the neonatal period. Additionally, the evaluation of MOD may be affected by TH considering its multiorgan effects.